Pengaruh Motivasi, Pelatihan dan Salary Terhadap Kinerja Karyawan di PT. Eka Rahayu Azzahra - Meli Meli; Adiyan Andansyah; Muhammad Kosim; Muhammad Hasbi Hafidzalloh; Ridwan Zaenal Arifin; Nabila Agustina; Aulia Annisa Yuliani (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study analyzes the influence of motivation, training, and salary on employee performance at PT. Eka Rahayu Azzahra both partially and simultaneously. Using quantitative approach with a population of 20 employees, saturated sampling technique, and Likert scale questionnaire. Data analysis employed multiple linear regression with t-test and F-test.Results show: (1) Motivation positively and significantly affects employee performance (sig. 0.008 < 0.05; t count 3.031 > 2.120); (2) Training positively and significantly affects employee performance (sig. 0.005 < 0.05; t count 2.699 > 2.120); (3) Salary positively and significantly affects employee performance (sig. 0.000 < 0.05; t count 4.922 > 2.120); (4) Simultaneously, all three variables positively and significantly affect employee performance (sig. 0.008 < 0.05; F count 19.993 > 3.239). Salary is the most dominant factor. The study recommends integrated strategies to optimize performance through enhanced motivation, continuous training, and compensation evaluation.